ҚАРАҚАЛПАҚ ХАЛЫҚ ПЕДАГОГИКАСЫ ТИЙКАРЫНДА МЕКТЕПКЕ ШЕКЕМГИ ДӘЎИРДЕГИ БАЛАЛАРДЫҢ КРЕАТИВ ҚӘБИЛЕТИН РАЎАЖЛАНДЫРЫЎДА ЖУМБАҚЛАРДЫҢ ӘҲМИЙЕТИ - Бекимбетова, Г. (FAN va JAMIYAT, 2016)
The article deals with the impact on the mental development of preschool children through riddles in Karakalpak folk pedagogy and the development of the relationship between parents and preschool teachers.